THE ROLE OF CHEVRON NIGERIA LIMITED IN COMMUNITY DEVELOPMENT EFFORT IN NIGER DELTA 2005-2011 - Putra, Mahendra; Rainy Priadarsini, Ni Wayan; Suwecawangsa, Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 2 (2024): JURNAL DIKSHI, 2024)
This study describes Chevron Nigeria Limited (CNL) in its efforts to improve people's quality of life. CNL is one of the oil companies operating in the Niger Delta. Multinational Corporation (MNC) is a company whose operations involve one or more countries, CNL is one of the MNCs that seeks to deal with social and economic problems in the Niger Delta. The oil industry produces many profits for Nigeria. But on the other hand, oil exploration and production causes pollution. The environmental damage that occurs in the Niger Delta causes various problems for the community such as poverty, unemployment and lack of adequate public facilities. CNL as an MNC must implement Corporate Social Responsibility (CSR) as a form of responsibility and goodwill towards the host country. CNL implements Community Development through the Global Memorandum of Understanding (GMOU). Then GMOU produced Regional Development Committees (RDCs). RDC has the authority to spend and manage projects related to health, education, employment and infrastructure. Through this RDC the GMOU program by CNL is implemented. This study describes the efforts to implement CSR by CNL in the form of Community Development. The data in this study were analyzed using a qualitative descriptive method with secondary data sources and the concept of Corporate Social Responsibility and the concept of Community Development.